Predictive Relation between Early Numerical Competencies and Mathematics Achievement in First Grade Portuguese Children - Marcelino, Lilia; de Sousa, Óscar; Lopes, António (Frontiers in Psychology, 2017)
Early numerical competencies (counting, number relations, basic arithmetic operations) have a central position in the initial learning of mathematics, and their assessment is useful for predicting later mathematics achievement. Using a linear regression model, this study aims to analyse the correlational and predictive evidence between early numerical competencies and mathematics achievement in first grade Portuguese children (n = 123). The children’s early numerical competencies were examined at the point of school entry. Three criterion groups (low, moderate, high early numerical competencies) were formed based on the results of the early numerical screener and mathematics achievement measured at the end of first grade. The following hypotheses were tested: children who started first grade with low numerical competencies remained low mathematics achievement at the end of first grade; and children who started with high numerical competencies, finished the first grade with high mathematics achievement. The results showed that early numerical competencies contributed to a significant amount of explained variance in mathematics achievement at the end of the first grade. Children with low numerical competencies performed lower than children with moderate and high numerical competencies. Findings suggest that early numerical competencies are meaningful for predicting first-grade mathematics difficulties.